MIM REGULATES THE TRAFFICKING OF BONE MARROW CELLS VIA MODULATING SURFACE EXPRESSION OF CXCR4 - Zhan, Tailan (Leukemia, 2016)
Missing in metastasis (MIM) is abundantly expressed in hematopoietic cells. Here we characterized the impact of MIM deficiency on murine bone marrow (BM) cells. Although MIM(-/-) cells proliferated similarly to wild type (WT), they exhibited stronger response to chemokine SDF-1, increase in surface expression of CXCR4, impaired CXCR4 internalization and constitutive activation of Rac, Cdc42 and p38. Transplantation of MIM(-/-) BM cells into lethally irradiated mice showed enhanced homing to BM, which was abolished when mice were pretreated with a p38 antagonist. Interestingly, MIM(-/-) BM cells, including hematopoietic stem and progenitor cells (HSPCs), showed 2 to 5-fold increase in mobilization into the peripheral blood upon treatment with AMD3100. In vitro, MIM(-/-) leukocytes were susceptible to AMD3100 and maintained increased response to AMD3100 for mobilization even after transfer into wild type mice. MIM(-/-) mice had also a higher level of SDF-1 in the circulation. Our data highlighted an unprecedented role of MIM in the homoeostasis of BM cells, including HSPCs, through modulation of the CXCR4/SDF-1 axis and interactions of BM leukocytes with their microenvironments.